Deltacoronavirus Evolution and Transmission: Current Scenario and Evolutionary Perspectives - Vlasova, Anastasia N.; Kenney, Scott P.; Jung, Kwonil; Wang, Qiuhong; Saif, Linda J. (Frontiers in Veterinary Science, 2021)
Deltacoronavirus (DCoV)–the only coronavirus that can infect multiple species of mammals and birds–was initially identified in several avian and mammalian species, including pigs, in China in 2009–2011. Porcine DCoV has since spread worldwide and is associated with multiple outbreaks of diarrheal disease of variable severity in farmed pigs. In contrast, avian DCoV is being reported in wild birds in different countries without any evidence of disease. The DCoV transboundary nature and the recent discovery of its remarkably broad reactivity with its cellular receptor–aminopeptidase N (APN)–from different species emphasize its epidemiological relevance and necessitate additional research. Further, the ability of porcine DCoV to infect and cause disease in chicks and turkey poults and gnotobiotic calves is suggestive of its increased potential for interspecies transmission or of its avian origin. Whether, porcine DCoVs were initially acquired by one or several mammalian species from birds and whether avian and porcine DCoVs continue co-evolving with frequent spillover events remain to be major unanswered questions. In this review, we will discuss the current information on the prevalence, genetic diversity, and pathogenic potential of porcine and avian DCoVs. We will also analyze the existing evidence of the ongoing interspecies transmission of DCoVs that may provide novel insights into their complex evolution.